PELUANG DAN TANTANGAN G20 DALAM TRANSFORMASI MANAJEMEN PENDIDIKAN DI ERA REVOLUSI INDUSTRI 4.0 DAN CIVIL SOCIETY 5.0 PASCA PANDEMI COVID-19 - ELIYUNUS WARUWU; AYLER BENIAH NDRAHA; DELIPITER LASE (LP2MTBM MAKARIOZ, 2022)
The pandemic that has occurred from 2020 until now has had an impact on every sedimentation of human life. No country in the world is not affected by this, the difference is the percentage affected. People who fill the power of a country during the Covid-19 pandemic have an attitude that is able to translate responsively and innovatively, so they need to be given a big stage for accelerating the recovery of the country's condition. During his presidency, Indonesia played a role in setting priority agendas and chairing a series of G20 meetings. «Recover Together, Recover Stronger» is a big theme raised by the G20 Indonesia presidency this time. Qualitative research-based observation and empiricism. The era of disruption that is being experienced by the State of Indonesia coupled with the Covid-19 pandemic has brought a blessing in disguise, especially in the education sector. The education sector in Indonesia, which was previously still semi-modern systematic, even in developing areas, is still carried out conventionally with minimal touch of digitization. The Future of the World of Work After the Covid-19 Pandemic The world's needs, especially the post-Covid-19 world of work, have changed. Therefore, the world must reorganize how education can answer the challenges of the future world. These four issues need to be sharpened by coordination and consolidation with the Sherpas and need to be triggered by a good response. The challenges of education in the era of technological disruption or the development of technology and information science can be concluded that with these developments it should make it easier for the development of the world of education. However, what happened was just the opposite, as explained above that there are many challenges that teachers must face in carrying out their duties as teachers in the era of technological disruption. However, the situation will be different if the teachers are able to understand the challenges and how to overcome them, then the world of education will experience advanced development together with technological developments.